Yellow mite of jute Problem and its management - Satpathy, S; Babu, V Ramesh (Indian Farming, 2024)
The pest status of yellow mite has gradually enhanced in jute which is mainly due to excessive reliance of chemical pesticides and favourable weather condition for mite during the early growth phase of the crop. Comprehensive adoption of proper management strategy for jute mite is very important to reduce the cost of protection and increasing the fibre yield and quality. The integratedpest management (IPM) strategy involving proper sowing time, tolerant variety, line sowing, balanced nutrition, need based use of entomopathogens and new safer acaricides is important for sustainable management of yellow mite in jute.